Small and Medium Micro Enterprise Development Strategy (MSMEs) Kletekan Village Through Digital Marketing - BRENDA ANNISA VINURI (BALE LITERASI, 2022)
This community service activity aims to increase the knowledge and economic value of MSME actors through digital marketing strategies and provide training on making creative and innovative products for rambutan jam for the people of Kletekan Village. Service activities are carried out through counseling, discussion, and practice methods. The extension method is carried out by delivering digital marketing strategy materials to MSME actors. The discussion method is carried out by case studies, sharing experiences, and providing suggestions and input. While the practical method is carried out by applying the knowledge that has been possessed, namely practicing how to use social media and e-commerce as a means of product marketing as well as the practice of making creative and innovative rambutan jam products. The results of the activity show that efforts to increase the economic value of MSME actors through digital marketing strategies and training on making creative and innovative products are focused on five things, namely problem identification, the importance of branding and business legality, product packaging, attractive catalogs, and advertisements. The impact of the training activities for making rambutan jam can increase the knowledge and skills of the village community in processing rambutan into an economic product that is worth selling. Extension activities and training on creative and innovative products in Kletekan Village are very useful and are expected to be sustainable.